In-vitro α-amylase and α-glucosidase inhibitory activity of coccinia grandis fruits and hyptis suaveolens seeds extracts (Journal of Pharmaceutical Negative Results, 2023)
Introduction Diabetes mellitus is a chronic metabolic illness that has a significant health and economic impact on society. Current diabetes treatments are expensive and reported to have side effects on long-term use. The use of ethnomedicinal plants has showed promise in the creation of less expensive, cost-effective anti-diabetic medicines with fewer adverse effects. The plants Coccinia grandis and Hyptis suaveolens have been used in Ayurvedic medicine to treat microbial infections, gastrointestinal issues, inflammation, diabetes, helminthiasis, and hyperuricemic conditions.Methods: Hydro alcoholic extracts of Coccinia grandis fruits and Seeds of Hyptis suaveolens were prepared and their inhibitory actions of these extracts on α-amylase and α-glucosidase inhibitory activities was determined in vitro.Results: The results indicated concentration-dependent inhibitory action with both the extracts on the enzyme alpha amylase and alpha glucosidase However, coccinia grandis fruit extract exhibited more α-amylase and α -glucosidase enzyme inhibition when compared with hyptis suaveolens seed extract.Conclusion: The results show that hydroalcoholic extracts of Coccinia grandis fruits and seeds of Hyptis suaveolens significant α-amylase and α -glucosidase inhibitory actions in vitro, according to the current research.